The more the better? An appraisal of combination therapies for actinic keratosis. (11th November 2019) - Steeb, T.; Wessely, A.; Leiter, U.; French, L.E.; Berking, C.; Heppt, M.V.
Abstract: Actinic keratoses (AK) are common precancerous lesions of the skin. Numerous interventions exist for the treatment of AK, including lesion‐ and field‐directed approaches. In daily practice, different treatment modalities are often combined to maximize clearance rates. However, whether a combination therapy is preferable to monotherapy in terms of efficacy and safety has been subject of intense debate. In this review, we summarize the current knowledge on the efficacy and safety of local combination therapies for the treatment of patients with AK. Combination approaches of cryosurgery followed by photodynamic therapy (PDT), laser‐assisted PDT, PDT in combination with topical interventions and microneedling‐assisted PDT have shown slightly better efficacy results with similar tolerability compared to the respective monotherapy. However, the individual usage of combination therapies should be checked on a case‐by‐case basis and take into account individual patient‐ and lesion‐specific aspects as more resources are needed and because the individual monotherapies are already highly effective.